WAYANG TOPENG MALANG DALAM PERUBAHAN KEBUDAYAAN - Robby Hidajat (Imaji, 2012)
Musk puppet in Malang has a very special and distinctive presentation, that is consisting of some parts or acts in the forms of scenes: the Gending Giro traditional music, follwed with an opening dance Tari Patih, Jejeran, Grebek, Tari Bapang and Tari Gunungsari, ended with the scene of the meeting between Panji Asmarabangun and Candrakirana. The development of mask puppet in Malang as a cultural expression is very much influenced by the aspects of time, environment, and technological development especially information technology.